Physical and chemical characterization of sewage sludge with different proportions of diatomaceous earth - Mendes Braga, Fabíola; Cardoso Barbosa, Mário Henrique; Alves Oliveira, Ely Sandra; de Paula Sousa, Izabelle; Barbosa dos Santos, Claudiana; Arruda Sampaio, Regynaldo (Revista Ceres, 2025)
The use of residues for agricultural production is an alternative for the achievement of sustainability. When mixed with diatomaceous earth (DE) from biofuel filtration, sewage sludge (SS) plays an important role as soil conditioning agent. As a result, the objective of this work was to make a DE vermicompost at different proportions: 0; 7.53; 15.06; 22.59 and 30.12% v/v in relation to a SS pre-compost (PC) and gardening pruning residues. The experiment was carried out in 100-L containers in a randomized block design, with 5 treatments and 5 replications, in which Eisenia foetida earthworms were used in the pre-composting and vermicomposting processes. After four months, the physical characteristics of the vermicompost were analyzed. It was verified that the diatomaceous earth can be vermicomposted, even when soaked in biofuel oil, at amounts of up to 30.12% v/v, with no visible physical damage to earthworms and plants, and this proportion of DE reduced the concentration of nutrients, but improved the physical properties of the vermicompost, making it an excellent physical conditioner for use as a substrate of plants and fertilization of soils.